The Relationship Between Knowledge and Host Behavior With Pulmonary Tuberculosis Cases in the Productive Age in Rantau Alai District, Ogan Ilir Regency - Arindi Dinda Hanifah; Rahmatillah Razak; Elvi Sunarsih; Anggun Budiastuti (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Pulmonary tuberculosis is an infectious disease that is a health problem in the world. In Indonesia, most cases of tuberculosis attack the productive age. Cases of pulmonary tuberculosis in Rantau Alai District in 2022 amounted to 380 cases, with the number of positive cases as many as 29 cases resulting in disability in the lungs and extrapulmonary organs and even death. The purpose of this study was to analyze the relationship between knowledge and behavior of the host with the incidence of pulmonary tuberculosis at productive age in Rantau Alai Subdistrict, Ogan Ilir Regency. This study used a case-control design with 108 respondents selected by simple random sampling. Then, the data analysis test was carried out, namely the chi-square test and multiple logistic regression test. The results showed that there was a significant relationship between knowledge (p-value<0.001), smoking history (p-value>0.001), household contact (p-value<0.001), the habit of drying mattresses (p-value<0.001) and the habit of opening windows every morning (p-value<0.001) against pulmonary tuberculosis. The results of multivariate analysis showed that the variable of house contact (p-value 0.001) was the most dominant variable associated with pulmonary tuberculosis (OR= 15.059, 95% CI: 3.093-73.317). The conclusion of this study is that poor knowledge and behavior of the host can increase the risk of pulmonary tuberculosis. Suggestions for the community are expected to follow extension activities on an ongoing basis and implement clean and healthy living behaviors to prevent the proliferation of pulmonary tuberculosis bacteria.